Periclimenes sulcatus sp. nov., a new pontoniine shrimp (Crustacea: Decapoda: Palaemonidae) from Vietnam - Ďuriš, Zdeněk; Horká, Ivona; Marin, Ivan (Zootaxa, 2008)
We describe and illustrate a new species of pontoniine shrimp, Periclimenes sulcatus. This new species is unique among the shallow water Periclimenes species in having multiple dorsal telson spines, from four to six pairs. A relatively large and swollen faceted accessory pigment spot on the eyestalk, a subtriangular process on the fourth thoracic sternite, and a feebly developed second pair of chelipeds, only slightly larger than the first pair, are among other remarkable characteristics of this new species. The new species was collected in southeastern Vietnam, the South China Sea, in shallows at low tide. It densely inhabits seagrass meadows, but also occurs on other substrata down to 4 m.